Effect of Dietary Counselling on Anthropometric Measurements of Liposuction Patients - Khan, Adeela Jehan; Mohmand, Humayun; Bushra, Shafaq; Sajid, Sadaf; Jehan, Tooba; Kashif, Seemin (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: To observe the effects of dietary counselling on various anthropometric parameters in patients after liposuction. Methodology: This non-randomized educational intervention study was performed at a cosmetic surgery centre in Islamabad, Pakistan, from July to December 2017. Among 83 subjects, 43 were in the intervention group, and 40 were in the control group from both genders. Patients undergoing primary liposuction, abdominal liposuction, and abdominoplasty with liposuction were included in this study; patients on any weight loss diet or pills in the last six months were excluded. The intervention group was followed up three months after dietary counselling, and the control group was without dietary advice. Anthropometric measurements of both groups were done before liposuction, just after liposuction, and then three months after surgery, which included body weight, body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), and mid-upper arm circumference (MUAC). Data analysis was done with SPSS version 20. Results: Significant changes were found in all parameters except for MUAC in the control group. Independent-sample T-tests showed no statistically significant difference in any parameter at any time. Conclusion: Liposuction resulted in a reduction in weight, BMI, WC, WHR, and WHtR in both groups, but dietary counselling could not show its effect on any parameter in our study. Further reduction of these parameters in the intervention group could occur if the intervention lasted longer.